Computation of shortest path problem in a network with SV-trapezoidal neutrosophic numbers - Broumi, Said; Bakali, Assia; Talea, Mohamed; Smarandache, Florentin; Vladareanu, Luige (International Conference on Advanced Mechatronic Systems, 2016)
In this work, a neutrosophic network method is proposed for finding the shortest path length with single valued trapezoidal neutrosophic number. The proposed algorithm gives the shortest path length using score function from source node to destination node. Here the weights of the edges are considered to be single valued trapezoidal neutrosophic number. Finally, a numerical example is used to illustrate the efficiency of the proposed approach.